ON THE NON-TRUE ELEMENTS OF THE RIGHT-POLITICAL DISCOURSE - HAKOBYAN, GEVORG (Բանբեր Երևանի համալսարանի. Փիլիսոփայություն, Հոգեբանություն, 2020)
The article attempts to describe and comprehend such non-true elements of the right-political discourse which has not yet been comprehended and named. For this purpose, some types of non-true in the political discourse are discussed, which are named, comprehended, and explained. An analysis of these known types of non-true shows that none of them expresses the essence of the phenomenon described here and presented as an example in the context of the Artsakh-Azerbaijan conflict.